Scale of risk factors associated with emotional exhaustion in innovative educational environments: psychometric study of teachers - Beltran-Sanchez, Jesus Alfonso; Dominguez, Angeles; Moral de la Rubia, Jose (Frontiers in Education, 2024)
Educational innovation is a defining feature within educational institutions, necessitating a heightened emphasis on its promotion. However, exposure to these processes and participation tend to be highly demanding and exhausting for the teachers. Consequently, it becomes imperative for educational authorities to proactively monitor teachers' involvement in innovation, utilizing appropriate instruments to identify and assess the associated risk factors. This study proposes a rigorously validated and reliable model for measuring the risk factors associated with emotional exhaustion among teachers in innovative educational environments. Employing a cross-sectional design, the study scrutinized the psychometric properties of a sample comprising 535 university teachers from the same higher education institution actively engaged in educational innovation. The results from the investigation revealed that the measurement model demonstrated robust evidence of construct validity, as ascertained through both Exploratory and Confirmatory Factor Analysis. Predictive validity was evaluated utilizing Path Analysis, while convergence validity was assessed via Average Variance Extracted. Discriminant validity was established through the Homotrait-Heterotrait ratio, and gender invariance was validated through nested-model sequencing methods. Additionally, reliability assessments were conducted using both Cronbach's alpha and McDonald's omega coefficients. The resultant measurement model, characterized by its parsimony, offers educational institutions a valuable instrument for safeguarding faculty well-being amidst the demands of educational innovation.